Optimizing the Use of Natural Lighting - Pasau, Rayanda; Al Asy'Ary, Muhammad Farid; Sabudu, Maurice (CV. Gio Architect, 2024)
Lighting constitutes a crucial element in spatial design aimed at enhancing user comfort. However, the efficacy of natural lighting in buildings remains suboptimal due to prevalent preferences for artificial illumination. This study identifies instances where the utilization of natural lighting, particularly sunlight, can be optimized, focusing on the Dean building of the Faculty of Engineering Unsrat, specifically the Library room, also known as the E-Library room. The objective is to investigate the most effective timing for natural lighting usage compared to artificial lighting from lamps.